2019
DOI: 10.30607/kvj.494891
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adding Erythritol to Farrell Medium for Primary Isolation of the Brucella melitensis Strains

Abstract: This study aims to evaluate the addition of erythritol to Farrell medium (FM) for the primary isolation of B.melitensis strains. Selective media, particularly FM, is commonly used for Brucella isolation. Isolation is the gold standard for the diagnosis of brucellosis. The isolation success of selective media depends on their ingredients. Isolation rate may decrease particularly in contaminated samples; therefore, the addition of components like erythritol that augments the growth of Brucella species on media c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Higher concentrations of activated charcoal were considered unsuitable, since they allowed the growth of contaminant microorganisms and impaired the translucence for Brucella colony identification. These facts, together with the faster growth of all brucellae colonies in Bru SIC than in FM, CM, and BSM, indicate that Bru SIC can be highly recommended as an alternative medium ( 34 , 37 , 49 ). Activated charcoal has been occasionally used in bacterial culture due to its detoxifying properties ( 30 , 51 , 52 ), but to our knowledge it has never been applied for the identification of Brucella .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Higher concentrations of activated charcoal were considered unsuitable, since they allowed the growth of contaminant microorganisms and impaired the translucence for Brucella colony identification. These facts, together with the faster growth of all brucellae colonies in Bru SIC than in FM, CM, and BSM, indicate that Bru SIC can be highly recommended as an alternative medium ( 34 , 37 , 49 ). Activated charcoal has been occasionally used in bacterial culture due to its detoxifying properties ( 30 , 51 , 52 ), but to our knowledge it has never been applied for the identification of Brucella .…”
Section: Discussionmentioning
confidence: 89%
“…In addition to a higher recovery of CFU, the activated charcoal promoted a faster growth of Brucella colonies in Bru SIC, avoiding false-negative results arising from insufficient incubation, as described for B. ovis or B. suis cultures in FM ( 17 , 19 ). Another previously proposed strategy to promote Brucella growth in selective culture media is the addition of enrichment components such as erythritol ( 34 , 49 ). Interestingly, we observed that the substitution of calf serum by activated charcoal in Bru SIC allowed the successful isolation of more demanding Brucella strains, such as B. ovis PA.…”
Section: Discussionmentioning
confidence: 99%
“…It was intriguing that, if erythritol could promote B. melitensis growth in broth culture, it did not also promote bacterial development inside macrophages [ 12 ]. Erythritol was found to be a suppressor of intracellular growth in earlier studies looking at how it affected intracellular B. abortus in cow trophoblasts, though these studies never compared growth with and without erythritol in the culture medium [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Te presence of a growthstimulatory substance, eventually identifed as the 4carbon sugar erythritol [11], in the fetal tissues was determined to be the cause of this abnormally high bacterial count. Te inability of the B. abortus vaccine strain S19 to use erythritol as a carbon source was formerly thought to be directly linked to the virulence of the organism [12]. Recent research [13][14][15] suggests there may be a relationship between erythritol and virulence, albeit this correlation was not as strong as frst thought.…”
Section: Introductionmentioning
confidence: 99%